Analisis Faktor Risiko Yang Berkontribusi Terhadap Kejadian Tuberkulosis Paru di Masyarakat: Studi Epidemiologis Dan Implikasinya Dalam Pencegahan - Findi Septiani; Selvia Dewi Pohan; Herdita Br Ginting; Lestari Novianti Sinurat; Monica Triyuni Sinaga; Widya Kartini Pangaribuan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Tuberculosis (TB) remains one of the main challenges in the health sector in Indonesia, with a fairly high number of cases each year. This study aims to analyze the distribution of TB cases based on occupation and identify community groups that are at higher risk of spreading this disease. The data used in this study were obtained from estimates of the 2022 TB epidemiology report. The results of the analysis show that informal workers, such as laborers and traders, are the group with the highest number of TB cases, at 36.0%. This is followed by formal workers (21.6%), farmers/fishermen (17.3%), housewives (14.4%), students (6.5%), and unemployed or retired groups (4.2%). The high prevalence of TB in informal workers is caused by several factors, including an unhygienic work environment, limited access to health services, and unhealthy lifestyles. Based on these findings, a more effective strategy is needed in efforts to prevent and control TB, especially for groups with high levels of vulnerability. Health education, increasing access to health services, improving work environment sanitation, and early detection programs are important steps in reducing the spread of TB. With the right intervention, it is hoped that the number of TB cases in Indonesia can be reduced significantly.